The Health Impact Associated with Stress of Nurse Practitioners Working during COVID-19 Pandemic - Sarapat, Wiwat (Journal of The Department of Medical Services, 2024)
Background: Since 2019, nurse practitioners had been enduring and persevering during the COVID-19 pandemic. While the number of patients had been increasing, healthcare staff numbers remained the same. This brought stress to the staff and later caused health problems. Objective: To study the health impact associated with stress of nurse practitioners working during COVID-19 pandemic. Method: This was a survey study comprising of personal information and Stress Scale (PSS-10) evaluation. Result: The sample population was a total of 119 nurse practitioners responsible for COVID-19 screening for patients in Ubon Ratchathani Province. The samples had a mean age of 37.9±8.6 years and a mean year of working experience 15.6±8.7 years. Evaluation among 119 samples, the PSS-10 demonstrated 73 (61.3%) having a moderate level of stress and 46 (38.7%) with a mild level of stress. The health impact survey showed that 71 people (59.7%) having regular physical activity, 29 people (21.8%) having no regular physical activity, 109 people (91.6%) not drinking alcohol, all people not smoking, 90 people (59.7%) having no trouble in sleeping, 20 people (16.8%) waking up in the middle of the night. The relationship between the mentioned survey and level of stress was at 0.05 of the statistical significance only for the health perception, 97 people (81.5%) have the same health perception while 18 people (15.1%) feeling weaker. (R2 = .36, = -3.40 , p < .05). Conclusion: The research showed that nurse practitioners’ health perception during COVID-19 pandemic related to stress. Therefore, a policy to promote physical and mental health wellness would help reduce healthcare staff’s level of stress.